Penegakan Hukum Terhadap Pelaku KDRT Yang Dilakukan Anggota Militer Dan Perlindungannya Bagi Korban - Pramudita Antasia; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Domestic violence is an act that violates the law and disturbs public order. The fact that military members also engage in inappropriate behavior. Military Criminal Law and Law Number 23 of 2004 concerning the Elimination of Domestic Violence regulate domestic violence. (1) Domestic Violence According to Military Criminal Law, (2) Factors Causing Domestic Violence Committed by Military Members, and (3) Legal Protection for Victims of Domestic Violence According to Military Law. This research uses a descriptive approach. In addition, this research is included in the field of normative legal research, which includes an analysis of legal norms in the sense of law in the law. This research enhances our understanding of domestic violence committed by military members, the factors that cause domestic violence to occur, and how victims of domestic violence can obtain legal protection.